Global Innovation in Foreign Subsidiaries: The Impact of Entrepreneurial Orientation and Corporate Networks - Sidney Costa (FUCAPE Business School, 2017)
The article aims to show the differentiated moderating role of integration between the headquarters and subsidiary companies to explain the potential of local innovations becoming global innovations. Throughout the framework and hypotheses, we propose two global innovation development processes. In order to test them, we analyzed a sample of 172 subsidiaries from the structural equations technique to test the hypotheses and multiple-groups comparison in order to evaluate the moderating effect of subsidiaries embeddedness. The results confirm the adherence of a presented process: entrepreneurial orientation is associated with local innovation when moderated by embeddedness. In turn, this local innovation has great potential to become a global innovation. Another result diverged from the one presented in the hypotheses, but it has an important contribution. The result shows that the entrepreneurial orientation is associated with the inclusion of the subsidiary in the network, which has the potential of developing global innovation, but to do so it would have to be a radical or disruptive innovation.